Antihyperglycemic Test of Ethanol Extract of Soursop Leaf (Annona muricata L.) on Blood Sugar Levels of Male Mouse (Mus musculus) Induced by Glucose - Kusuma, Gusti Putu Okapanji Reza (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Soursop leaf (Annona muricata L.) is an herbal plant that is widely used by the public empirically because it has many properties. The sling leaf contains tannin compounds, alkaloids, as well as several other chemical compounds including annonaceous acetogenin, which can be used as a treatment. This study aims to find out if soursop leaf extract has the effect of deducting blood glucose levels in mice test animals (Mus musculus) which induced a 50% glucose solution. The study used the RAL method (complete random design) and 20 male mice were divided into 5 groups with 4 repetitions. Group P1, P2, and P3 (treatment group) administered ethanol extract of sine leaves at doses of 250, 500, and 750 mg/kg bb respectively, while k- and k+ (control group) administered CMC 0.5% and glibenclamide with oral administration. The data obtained were statistically analyzed with ANOVA (Variance analysis) one-way to find out the differences between treatment groups and continued with the BNT test (The smallest real difference) to find out meaningful differences between groups. The results showed that there were differences between the treatment group and the control group. On the 7th day of the BNT test, the treatment group with a dose of 750 mg/kg bb showed significant differences between the negative Control group (CMC 0'5%), Positive control (Glibenclamide), P1 (250 mg/kg bb), and P2 (500 mg/kg bb), while on the 14th day showed no significant difference with the treatment group of 500 mg/kg bb. concluded from this study that all concentrations of ethanol extract of sling leaves could lower blood glucose levels in test animals, with the most optimal decrease being the group at a dose of 750 mg/kg bb.